Odpowiedzi

2009-12-08T20:05:22+01:00
1)xa-2bx+ya-2by
2)16x²+8xy+y²
3)x²-1
4)(x+y)²
5)(5a-6b)²
6)m²-16n²
7)289
8)899
2009-12-08T20:06:40+01:00
X(a-2b)+y(a-2b)=xa-2xb+ya-2by
(4x+y)^= = 16x²+8xy+y²
(x-1)(x+1)=x²-1
x^+2xy+y^=(x+y)²
25a^-60ab+36b^=(5a-6b)²
m^-16n^=m²-(4n)²
17^=189
31*29=899
2009-12-08T20:07:21+01:00
Zakłam że to ^ zanaczy "do kwadratu"

x(a-2b)+y(a-2b)=ax-2bx+ay-2by
(4x+y)^=16x²+8xy+y²
(x-1)(x+1)=x²-1
x^+2xy+y^=(x+y)²
25a^-60ab+36b^=(5a-6b)²
m^-16n^=m²-16n²
17^=289
31*29=899
_____________
Rozdaje zaproszenia na lockerz.com
wystarczy podać mi e-maila